2020
DOI: 10.3390/jdb8020008
|View full text |Cite
|
Sign up to set email alerts
|

Delta-Notch Signaling: The Long and the Short of a Neuron’s Influence on Progenitor Fates

Abstract: Maintenance of the neural progenitor pool during embryonic development is essential to promote growth of the central nervous system (CNS). The CNS is initially formed by tightly compacted proliferative neuroepithelial cells that later acquire radial glial characteristics and continue to divide at the ventricular (apical) and pial (basal) surface of the neuroepithelium to generate neurons. While neural progenitors such as neuroepithelial cells and apical radial glia form strong connections with their neighbours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…The role of Notch signaling in regulating the balance between proliferation and cell cycle exit in retina neurogenesis is well-established (Moore and Alexandre, 2020 ). Furthermore, Notch activity correlates with nuclear position: within RPCs, Notch activity increases as the nucleus approaches the apical surface (Del Bene et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of Notch signaling in regulating the balance between proliferation and cell cycle exit in retina neurogenesis is well-established (Moore and Alexandre, 2020 ). Furthermore, Notch activity correlates with nuclear position: within RPCs, Notch activity increases as the nucleus approaches the apical surface (Del Bene et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism unraveled here is akin to lateral inhibition, well known in developmental systems, where it also frequently involves Notch signaling ( Moore and Alexandre, 2020 ; Sjöqvist and Andersson, 2019 ). Previous work also described Delta-like 1 (DLL1)-mediated feedback from aNSCs and/or aNP equivalents in the SEZ ( Ables et al., 2010 ; Kawaguchi et al., 2013 ), and we extend these findings by highlighting the spatiotemporal relevance of this mechanism in adult NSC niches.…”
Section: Discussionmentioning
confidence: 98%
“…In mammals, there are four different Notch receptors that are activated by ligands belonging to the family of Delta-like and Jagged proteins (Brittan and Wright, 2007). Ligand binding induces cleavage of the intracellular domain, which enters the nucleus and activates transcription of target genes (Moore and Alexandre, 2020). A small amount of evidence has indicated that loss of the key transport proteins Kif3a and IFT88 results in disruption of Notch signaling in cultured keratinocytes and the intact epidermis.…”
Section: Notchmentioning
confidence: 99%